Evidence for spatially-responsive neurons in the rostral thalamus - Jankowski, Maciej M.; Passecker, Johannes; Islam, Md Nurul; Vann, Seralynne; Erichsen, Jonathan T.; Aggleton, John P.; O’Mara, Shane M. (Frontiers in Behavioral Neuroscience, 2015)
Damage involving the anterior thalamic and adjacent rostral thalamic nuclei may result in a severe anterograde amnesia, similar to the amnesia resulting from damage to the hippocampal formation. Little is known, however, about the information represented in these nuclei. To redress this deficit, we recorded units in three rostral thalamic nuclei in freely-moving rats (the parataenial nucleus, the anteromedial nucleus and nucleus reuniens). We found units in these nuclei possessing previously unsuspected spatial properties. The various cell types show clear similarities to place cells, head direction cells, and perimeter/border cells described in hippocampal and parahippocampal regions. Based on their connectivity, it had been predicted that the anterior thalamic nuclei process information with high spatial and temporal resolution while the midline nuclei have more diffuse roles in attention and arousal. Our current findings strongly support the first prediction but directly challenge or substantially moderate the second prediction. The rostral thalamic spatial cells described here may reflect direct hippocampal/parahippocampal inputs, a striking finding of itself, given the relative lack of place cells in other sites receiving direct hippocampal formation inputs. Alternatively, they may provide elemental thalamic spatial inputs to assist hippocampal spatial computations. Finally, they could represent a parallel spatial system in the brain.